Isolation of a SARS-CoV-2 strain from pediatric patients in South Korea: biologic and genetic characterization - Chung, Hee Chun; Kim, Sung Jae; Hwang, Su Jin; Park, Sung Hoon; Park, Kyoung Min; Chung, Hyeon Woo; Ko, Si Hwan; Park, Dong il; Shim, Jun-Yeop; Nguyen, Van Giap; Lee, Jae Myun (Frontiers in Microbiology, 2025)
IntroductionPediatric isolates of SARS-CoV-2 remain underrepresented in virologic studies, despite their importance for understanding viral diversity and therapeutic responses.MethodsNasal swab and saliva samples were collected from pediatric COVID-19 patients. Viral isolation was attempted in Vero cells through five blind passages. Replication was assessed by digital RT-PCR, while cytopathic effects were observed microscopically. Genomic sequencing was conducted using next-generation sequencing, and antiviral activity was evaluated for Remdesivir, Molnupiravir, and Nirmatrelvir.ResultsA SARS-CoV-2 strain, designated N15, was successfully isolated from a pediatric nasal swab. The isolate replicated efficiently in Vero cells with kinetics comparable to B.1 and B.1.1.529 lineages. Cytopathic effects appeared within 48 h post-infection, marked by aggregates of dead cells. Genomic analysis classified N15 within lineage 19B, showing 99.9% similarity to the Wuhan-Hu-1 strain. Rare mutations were identified: N709S in the spike protein and T11M in the E protein. Antiviral testing revealed effective inhibition by Remdesivir, Molnupiravir, and Nirmatrelvir, with varying IC50 values across cell types.DiscussionThe pediatric N15 isolate represents a unique 19B lineage virus, retaining ancestral genomic features while harboring rare mutations. Its efficient replication and drug sensitivity underscore its value as a reference strain for comparative studies against circulating variants and for evaluating antiviral efficacy.